1987
DOI: 10.1007/bf02134045
|View full text |Cite
|
Sign up to set email alerts
|

Renal and cerebral necrosis in survivor after in utero death of co-twin

Abstract: A newborn with bilateral renal cortical necrosis and severe cerebral damage in association with a macerated stillborn twin is reported. The alterations in the kidneys and brain of the twin born alive suggest that the primary event took place before birth. Thromboplastic material and embolizing particles derived from the dead fetus may have passed the monoamnionic-monochorionic twin placenta and caused disseminated intravascular coagulation in the living twin, followed by infarction in other organ systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The combination of the ten series and all case reports published during the same time interval [22][23][24][25][26][27][28][29][30][31] does not provide conclusive evidence on which variables may affect the outcome of the survivor. It appears that there are no differences if single intrauterine death occurs in cases of twin-twin transfusion syndrome (11 intact survivors of 25) compared to cases where there were no echographic signs of twin-twin transfusion syndrome (nine of 15, not significant), but the number of pregnancies which can be analyzed for this purpose is clearly insufficient.…”
Section: The Surviving Twin: Review Of the Literaturementioning
confidence: 99%
“…The combination of the ten series and all case reports published during the same time interval [22][23][24][25][26][27][28][29][30][31] does not provide conclusive evidence on which variables may affect the outcome of the survivor. It appears that there are no differences if single intrauterine death occurs in cases of twin-twin transfusion syndrome (11 intact survivors of 25) compared to cases where there were no echographic signs of twin-twin transfusion syndrome (nine of 15, not significant), but the number of pregnancies which can be analyzed for this purpose is clearly insufficient.…”
Section: The Surviving Twin: Review Of the Literaturementioning
confidence: 99%
“…Many of the descriptions in the literature are also similar to the case here shown, but conclusive proof of prenatal DIC with de fi nitive coagulation studies has been dif fi cult to obtain. In a case of macerated MoMo twin with a term live-born co-twin, Bulla et al ( 1987 ) found neonatal platelet counts of 67,000/mm 3 that later rose to 300,000/mm 3 . The infant died on day 10 with bilateral renal, splenic, and central nervous system (CNS) necroses.…”
Section: Monoamnionic Monochorionic Twin Placentamentioning
confidence: 97%
“…The hypothesis of embolization is also highlighted by the five cases of monochorionic twins with sonographically diagnosed cerebral defects in survivors reported by Patten et al [31]. Among the numerous other cases reported, that of Bulla et al [6] is of interest. They decribed a neonate with cerebral and renal necrosis, associated with a macerated cotwin.…”
Section: Outcome Of the Surviving Twinmentioning
confidence: 91%